A multi-institutional analysis of minimally invasive liver resections - Smith, Alison; Konstantinidis, Ioannis T.; Fong, Yuman; Martinie, John; Iannitti, David; Buell, Joseph F. (Laparoscopic Surgery, 2018)
Background: As minimally invasive liver resection (MILR) gains acceptance, techniques, and outcomes must be analyzed in multi-institution series comparing both laparoscopic and robotic approaches to open liver resections (OLRs). The objective of this study was to describe the experience with MILR at three high volume centers. Methods: Retrospective tri-institutions analysis of MILR from 2000 to 2016. Patient demographics, tumor characteristics, and outcomes were analyzed for statistical significance compared to OLR. Results: A total of 1,323 patients were included with 746 OLR (56.4%) and 577 MILR (530 laparoscopic, 40.1%, and 47 robotic liver resections, 3.6%). MILRs increased during the study period (0.5%, year 2000, vs. 40.5%, year 2016, P